Alkis Charalampidis, Η ιταλική Αναγέννηση. Αρχιτεκτονική – Γλυπτική – Ζωγραφική [The Italian Renaissance: Architecture – Sculpture – Painting] - Drakopoulou, Eugenia (The Historical Review/La Revue Historique, 2015)
no abstract available